2007
DOI: 10.1177/0269881107079171
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Clozapine use in two women with schizophrenia during pregnancy

Abstract: Stabilized patients who receive clozapine may wish to have children; but studies on pregnant women receiving clozapine treatment are limited. In this study, we report on clozapine use during pregnancy in two women. The first woman (Case 1) had two deliveries while she was receiving clozapine treatment for schizophrenia. Both her deliveries were term, uncomplicated vaginal deliveries, and the clozapine dose was reduced throughout pregnancy. The second woman (Case 2) developed schizophrenia after her first child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Our results were consistent with some case reports and few studies [ 8 , 12 ], but not others [ 5 7 ]. Mendhekar [ 13 ] reported that an infant had delayed speech acquisition until 5 years old when the mother was taking clozapine during pregnancy and breast feeding period, but in our study we did not find any difference for language development between the two groups.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results were consistent with some case reports and few studies [ 8 , 12 ], but not others [ 5 7 ]. Mendhekar [ 13 ] reported that an infant had delayed speech acquisition until 5 years old when the mother was taking clozapine during pregnancy and breast feeding period, but in our study we did not find any difference for language development between the two groups.…”
Section: Discussionsupporting
confidence: 94%
“…However, there is sparse data on the reproductive safety of the currently available newer compounds. Up to now, most information about atypical antipsychotics on reproductive safety and the effects on infant development come from case reports, case series, and retrospective studies [ 5 7 ]. Very few studies compared the difference effects on infants’ development for clozapine and other atypical antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was not possible to conclude whether this neurodevelopmental difficulty was due to the use of clozapine or other factors. Others case reports on clozapine use during pregnancy have reported no complications or congenital anomalies [57,58]. concluded that exposure to risperidone does not increase pregnancy risks compared with those in women not taking the drug [50].…”
Section: Treatment During Pregnancymentioning
confidence: 99%
“…However, it was not possible to conclude whether this neurodevelopmental difficulty was due to the use of clozapine or other factors. Others case reports on clozapine use during pregnancy have reported no complications or congenital anomalies [57,58].…”
Section: Special Considerations During Pregnancy and The Postpartum Periodmentioning
confidence: 99%
“…Gestational diabetes mellitus, neonatal seizures, neonatal agranulocytosis, macrocephaly, shoulder dystocia, floppy infant syndrome, decrease foetal heart rate variability, atrial septum defect, gastroesophageal problems, and delayed peristalsis have been reported to have adverse outcomes in maternal exposure to clozapine during pregnancy [11][12][13][14][15][16][17][18][19][20]. On the other hand, some studies have reported that no adverse effects were found in the newborns [21][22][23]. Pregnancy period is not protective for schizophrenia, unlike may lead to relapse of a patient in remission.…”
Section: Discussionmentioning
confidence: 99%